1999
DOI: 10.1016/s0022-2275(20)32105-2
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol sulfate and calcium affect stratum corneum lipid organization over a wide temperature range

Abstract: The main diffusion barrier for drugs penetrating through the skin is located in the intercellular lipid matrix in the upper layer of the skin, the stratum corneum (SC). The main lipid classes in the SC are ceramides (CER), free fatty acids (FFA) and cholesterol (CHOL). The lipids in SC are organized into two lamellar phases with periodicities of approximately 13 and 6 nm, respectively. Similar lipid organization has been found with equimolar CHOL:CER:FFA mixtures in SAXD studies performed at room temperature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 38 publications
(58 reference statements)
1
28
1
Order By: Relevance
“…(ii) In X-linked ichthyosis skin a substantial increase in cholesterol sulfate level has been observed (Elias et al, 1984). In a previous study with pigCER it was shown that an increased level of cholesterol sulfate promotes the formation of a¯uid phase (Bouwstra et al, 1998a;Bouwstra et al, 1999). For this reason the elevated levels of cholesterol sulfate in X-linked ichthyosis skin are expected to promote the formation of a¯uid phase and possibly also to disturb the formation of the LPP.…”
Section: Discussionmentioning
confidence: 98%
“…(ii) In X-linked ichthyosis skin a substantial increase in cholesterol sulfate level has been observed (Elias et al, 1984). In a previous study with pigCER it was shown that an increased level of cholesterol sulfate promotes the formation of a¯uid phase (Bouwstra et al, 1998a;Bouwstra et al, 1999). For this reason the elevated levels of cholesterol sulfate in X-linked ichthyosis skin are expected to promote the formation of a¯uid phase and possibly also to disturb the formation of the LPP.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies (13,14,16) and the present study reveal that in CHOL:CER mixtures prepared with both pig and human CER the following similarities in phase behavior have been observed: a) In CHOL:CER mixtures the LPP is formed, demonstrating the formation of the same lamellar phases as present in intact SC; b) the phase behavior of CHOL:CER mixtures is not sensitive to changes in the CHOL:CER molar ratio over a wide range; c) in CHOL:CER mixtures hexagonal lateral packing is present. Addition of long chain FFA induces a transition from hexagonal to orthorhombic lateral packing; d) the presence of cholesterol sulfate increases the solubility of CHOL in CHOL: CER:FFA mixtures; and e) in mixtures prepared with HCER lacking HCER1 the formation of the LPP is strongly reduced, as observed with pigCER mixtures.…”
Section: Comparison Between Mixtures Prepared From Either Pigcer or Hcermentioning
confidence: 99%
“…This phase was less prominent or even absent in intact SC. From the experiments performed with mixtures prepared from pigCER it became clear that the fraction of lipids forming this phase at elevated temperatures decreased when at room temperature the amount of phase-separated CHOL was reduced (16). Such a situation can also be achieved by addition of cholesterol sulfate.…”
Section: Phase Behavior Of Hcer:chol Mixtures At Elevated Temperaturesmentioning
confidence: 99%
See 1 more Smart Citation
“…An acidic pH is critical for barrier homeostasis, in part because two key lipid-processing enzymes, b-glucocerebrosidase (bGlcCer' ase) and acidic sphingomyelinase, which generate a family of ceramides from glucosylceramide and sphingomyelin precursors, respectively (Uchida et al, 2002), exhibit low pH optima (Vaccaro et al, 1985;Holleran et al, 1993;Jensen et al, 1999;Schmuth et al, 2000). It has also been proposed that an acidic pH directly impacts lipidl ipid interactions in the SC extracellular lamellar bilayers (Bouwstra et al, 1999). Together, these mechanisms appear to regulate the competence of the extracellular lamellar bilayer system.…”
mentioning
confidence: 99%